Enhanced macroboring and depressed calcification drive net dissolution at high-CO(2) coral reefs - Enochs, Ian C. (Proc Biol Sci, 2016)
Ocean acidification (OA) impacts the physiology of diverse marine taxa; among them corals that create complex reef framework structures. Biological processes operating on coral reef frameworks remain largely unknown from naturally high-carbon-dioxide (CO(2)) ecosystems. For the first time, we independently quantified the response of multiple functional groups instrumental in the construction and erosion of these frameworks (accretion, macroboring, microboring, and grazing) along natural OA gradients. We deployed blocks of dead coral skeleton for roughly 2 years at two reefs in Papua New Guinea, each experiencing volcanically enriched CO(2), and employed high-resolution micro-computed tomography (micro-CT) to create three-dimensional models of changing skeletal structure. OA conditions were correlated with decreased calcification and increased macroboring, primarily by annelids, representing a group of bioeroders not previously known to respond to OA. Incubation of these blocks, using the alkalinity anomaly methodology, revealed a switch from net calcification to net dissolution at a pH of roughly 7.8, within Intergovernmental Panel on Climate Change's (IPCC) predictions for global ocean waters by the end of the century. Together these data represent the first comprehensive experimental study of bioerosion and calcification from a naturally high-CO(2) reef ecosystem, where the processes of accelerated erosion and depressed calcification have combined to alter the permanence of this essential framework habitat.